Answer: 1
=====================================================
Work Shown:
![\displaystyle L = \lim_(x \to 1) \left(\frac{a\text{x}^2+b\text{x}+c}{c\text{x}^2+b\text{x}+a}\right)\\\\\\\displaystyle L = (a(1)^2+b(1)+c)/(c(1)^2+b(1)+a)\\\\\\\displaystyle L = (a+b+c)/(c+b+a)\\\\\\\displaystyle L = (a+b+c)/(a+b+c)\\\\\\\displaystyle L = 1\\\\\\](https://img.qammunity.org/2023/formulas/mathematics/college/hehe0afolmvs83ud11jo18ghv6pyd9o9hq.png)
Therefore,
![\displaystyle \lim_(x \to 1) \left(\frac{a\text{x}^2+b\text{x}+c}{c\text{x}^2+b\text{x}+a}\right)=1](https://img.qammunity.org/2023/formulas/mathematics/college/3dd32u06culjuulpwbsxgqzyur5c5wshoh.png)
-------------------
Step-by-step explanation:
Apply substitution. Replace each copy of x with 1. We don't have to worry about division by zero errors in this case. After replacing x, we have a+b+c in the numerator and denominator, in which cancel to get us 1 as the final answer.